VIRTUAL WRITING FORUM WITH DON MURRAY AND THE NATIONAL WRITING PROJECT IN AN ASYNCHRONOUS ENVIRONMENT - Taylor, Joan (Online Learning, 2001)
This study evaluated the level of participation and perceptions of effectiveness and value among participants in a virtual forum interacting with one another and with Donald Murray, a noted mentor in writing instruction. National Writing Project teacher consultants were invited to participate in a two-week interactive session using Caucus®, a non-threaded, World Wide Web-based, asynchronous computer conferencing system. Eighty-one teacher-consultants responded and participated in the event. Using a multiple perspective framework, data gathered through surveys, interviews, transcript analysis and online discussions suggest that participants, project coordinators and directors, as well as the author himself, found the event a valuable learning experience with interesting possibilities.